LB1 Is higher perceived social support related to greater participation in cardiovascular disease (CVD) risk reducing behaviours for people with severe mental illnesses (SMI)?. (September 2018) - Burton, A; Walters, K; Osborn, D
Abstract : Background: The mortality gap for people with SMI from CVD is increasing. Studies have found a positive relationship between perceived social support and CVD outcomes in the general population; however there has been less research in people with SMI. Social support may influence CVD outcomes through encouraging participation in healthy lifestyle activities. Aims: To assess whether higher social support as measured by the Medical Outcomes Study–Social Support Survey (MOS-SSS) is associated with greater attendance at primary care intervention appointments. Secondary outcomes included: adherence to CVD medications (Morisky Medication Adherence Scale (MMAS)), physical activity (International Physical Activity Questionnaire (IPAQ)), diet (Dietary Instrument for Nutrition Education (DINE)) alcohol consumption (Alcohol Use Disorders Identification Test (AUDIT)), self–reported smoking behaviour Methods: Longitudinal and cross sectional studies involving 326 patients with SMI and raised CVD risk factors. Participants were recruited from 76 GP practices in England to a clinical trial assessing the effectiveness of a behavioural intervention for reducing CVD risk in people with SMI against routine GP practice care. Secondary data analysis used random effects linear regression models for continuous outcomes, logistic regression for binary outcomes, and Poisson/negative binomial regression models for count outcomes. Results: A weak association between social support and attendance at primary care intervention appointments was identified. As social support scores increased by one point, the appointment attendance rate increased by 0.5% (IRR=1.0053; 1.0001–1.0105, p=0.05). When sex, age, ethnicity, diagnosis and deprivation were entered into the model, this association decreased to 0.3% and was no longer significant (IRR=1.0032; 0.9980–1.0085, p=0.23). A strong association between social support and CVD medication adherence was identified. The odds of being in the moderate/high adherence group compared to the low adherence group increased by 3.9% with a one point increase on the MOS-SSS (OR=1.0385; 1.0176 to 1.0598, p<0.001). This association remained significant when sex, age, ethnicity, diagnosis and deprivation were included in the model (OR=1.0390; 1.0133–1.0648, p=0.003). No significant associations were identified between social support and physical activity, diet, alcohol or smoking. Conclusions: Social support may be an important facilitator for attendance at appointments and adherence to CVD medications; however no association was found between social support and lifestyle behaviours. Harnessing positive social relationships in the delivery of interventions for reducing CVD risk in this population should be considered as a strategy for encouraging uptake.